IMPLEMENTATION OF THE SUKATENDEL VILLAGE REGULATION POLICY NO. 01 OF 2019 CONCERNING THE DISASTER RESILIENT VILLAGE PROGRAM - Riri Rezeki Hariani; Neri Arisuma; Elga Rahayu (RADJA PUBLIKA, 2022)
Indonesia is an archipelagic country that is vulnerable to natural and non-natural disasters. The trend of natural disasters that occur in Indonesia itself tends to increase from year to year as well as what happened in Karo Regency. According to BPS data from 2015-2020 there was an increase in natural disasters, especially those caused by the eruption of Mount Sinabung.The problem that occurs is that Sukatendel Village is located in Tiganderket District, Karo Regency which has an altitude of 500 meters above sea level. This certainly increases the risk of disaster. The purpose of this study was to determine the effectiveness of implementing the Sukatendel Village Regulation No. 01 of 2019 regarding the Disaster Resilient Village program. With qualitative research methods. The results showed thatImplementation of Village Regulation No. 1 of 2018 concerning the disaster-resilient village program which includes 4 (four) factors, namely: The communication factor has not been carried out properly, due to the irregularity of socialization activities and the limitations of information communication tools to the surrounding community. The human resource factor is adequate in the implementation of DESTANA with the establishment of a village management and DRR Forum, but has limited budget and facilities in disaster management. The disposition factor or commitment owned by the implementor is good in carrying out its responsibilities as the implementer of the policy. The bureaucratic structure factor in the implementation of DESTANA has been directed and clear with the creation of a disaster management mechanism, the division and role of each team, but this is of course with the approval of the Karo Regency Government.